2006
DOI: 10.2478/s11535-006-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model for analysis of non-MHC genes that influence allogeneic response: recombinant congenic strains of OcB/Dem series that carry identical H2 locus

Abstract: Alloreactivity is the strongest known primary immune response. Its clinical manifestations are graft rejection, graft-versus-host disease and graft-versus-leukemia effect. The strongest stimulation by allogeneic cells is due to incompatibility at the major histocompatibility complex (MHC) genes. However, the non-MHC genes also participate in allogeneic response. Here we present a mouse model for study of the role of non-MHC genes in regulation of alloreactivity and show that they besides encoding antigens also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The observations of progeny having a phenotype, which is beyond the range of the phenotype of its parents, are not rare in traits controlled by multiple genes. It was observed in different tests of immune responses of RC strains in vitro [31] [35] and in vivo [28] , [36] . Similarly, analysis of gene expression from livers in chromosome substitution strains revealed that only 438 out of 4209 expression QTLs were inside the parental range [37] .…”
Section: Discussionmentioning
confidence: 97%
“…The observations of progeny having a phenotype, which is beyond the range of the phenotype of its parents, are not rare in traits controlled by multiple genes. It was observed in different tests of immune responses of RC strains in vitro [31] [35] and in vivo [28] , [36] . Similarly, analysis of gene expression from livers in chromosome substitution strains revealed that only 438 out of 4209 expression QTLs were inside the parental range [37] .…”
Section: Discussionmentioning
confidence: 97%
“…The BALB/cHeA-c-STS/A (CcS) and O20/A-c-B10.O20/Dem (OcB) series of strains were used previously for analysis of alloantigen response. The strain distribution pattern of magnitude of proliferative response in MLR of individual RC strains to stimulator cells of four different strains was almost identical, indicating that differences in responsiveness, rather than the alloantigenic difference itself, determine the magnitude of the response, and that the responsiveness to different MHC alloantigens is largely controlled by the same genes [ 19 , 20 ]. We have mapped previously two of these responsiveness genes, Alan1 and Alan2 (Alloantigen response 1, 2) located on chromosomes 17 and 4, respectively, that control differences in proliferative response to several alloantigens in CcS and OcB RC strains [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%